M.E. Kerr introduces Fell. - Kerr, M. E. (New York, N.Y. : Harper & Row, 1987)
A strange incident on the night of the senior prom changes John Fell's entire life, leading him to enroll in an exclusive private school under an assumed name.
"A Charlotte Zolotow book.".
Cover title: Fell.
Notable/Best Books (A.L.A.).
School Library Journal.
Wilson's Senior High School.
7.4
Keywords: Schools -- Fiction; Spies -- Fiction; School stories; Spies -- Fiction